Hyphessobrycon rutiliflavidus n. sp., a new characid fish from the upper rio Paraguai, State of Mato Grosso, Brazil (Characiformes: Characidae) - Carvalho, Fernando Rogirio; Langeani, Francisco; Miyazawa, Carlos Suetoshi; Troy, Waldo Pinheiro (Zootaxa, 2008)
Hyphessobrycon rutiliflavidus, new species, is described from the upper rio Paraguai in Cuiab<, State of Mato Grosso, Brazil. The new species differs from all other congeners by the following combination of characters: black humeral spot, slightly diffuse at its tips, and caudal-peduncle blotch present; midlateral body stripe conspicuous in its posteriormost portion, extending to the tips of the middle caudal rays; anal fin with iii,15 to iv,19 rays (mode iv,17); upper jaw length, 42.3 to 49.5% of the head length; maxilla with 2–5 teeth (mode 3); all the fins of males reddish-orange and of females yellowish.